Sharah-e-sehat: rahnumai-e-sehat (Kafayat publishers Karachi, 1999)
"Sharah-e-Sehat: Rahnumai-e-Sehat" explores the essential principles of health and wellness. It offers guidance on maintaining a balanced lifestyle, emphasizing nutrition, physical activity, and mental well-being. This concise work serves as a valuable resource for individuals seeking to improve their overall health and quality of life.